The Linguistic Image of the World and Image Schemas: an attempt at their delimitation and comparison - Carisio, Anastasiia (Complutense Journal of English Studies, 2020)
This article is a review of a few essential aspects of one of the famous Slavic linguistic schools —the Polish ethnolinguistic school of Lublin. This school developed the theory of językowy obraz świata (in Polish) or jazykovaja kartina mira (in Russian), which is generally translated in English as ‘Linguistic Image of the World’ (LIW). The Linguistic Image of the World takes into account the sociocultural embeddedness of language and cognition. We will compare this theory with embodiment models —Image Schemas. The paper is organised in four parts: (1) a brief review of relevant studies related to the Theory of Linguistic Image of the World; (2) an introduction to some essential aspects of Image Schemas, as representative of the standard Cognitive Linguistics approach, together with a brief analysis of some examples; (3) a description of LIW, highlighting some basic notions such as the stereotype and clarifying its relationship with the prototype; and (4) conclusions on the central role of culture in the process of conceptualization.